Institutional investors and stock price volatility: a literature review - Blaszke, Ewa (Inwestorzy instytucjonalni a zmienność cen akcji – przegląd literatury, 2021)
The purpose of this article is to provide an overview of some important literature on institutional investors. After several decades of study, no consensus has yet merged on whether institutional trading contributes to stock price volatility. There is also no clear answer to the question of whether the increase in volatility, if any, is due to herding behaviour among institutions. Despite the common perception that institutional managers follow each other into and out of the same securities and the strong theoretical foundations of herding, the results of empirical research on this matter are mixed. The article reviews the theoretical premises regarding the impact of institutions on stock prices and the most influential classic publications. The author also took into account the results of more recent studies, which focused not so much on herding behaviour but on the characteristics of institutional investors that could be considered important contributors to stock price volatility.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 2, s. 18-29
Keywords: institutional investors; herding behaviour; stock price volality; inwestorzy instytucjonalni; zachowanie stadne; zmienność cen